Problematic behaviors at mealtimes and the nutritional status of Brazilian children with Autism Spectrum Disorder - Soares, Rita de Cassia Santos; Cândido, Flávia Galvão; Filgueiras, Mariana De Santis; Rosa, Carla de Oliveira Barbora; Novaes, Juliana Farias de; Araujo, Raquel Maria Amaral (Frontiers in Public Health, 2024)
Objective The aim of this study was to explore problematic behaviors and their association with the food consumption and nutritional status of children with Autism Spectrum Disorder (ASD). Methods This is a cross-sectional study which enrolled 90 Brazilian children (aged 2–10 years) with ASD. A sociodemographic questionnaire, the ASD Eating Behavior Assessment Scale, and the 24-h recall were used. Age, height, total body weight, and Body Mass Index (BMI) were accessed to estimate nutritional status (BMI/Age). Consumption of fruits, vegetables, total calories, macro and micronutrients (calcium, iron, zinc, omega 3 and omega 6), and Body Mass Index (BMI) were assessed. The regression models were adjusted for covariates (prevalence ratio – PR, α = 0.05). Results All studied children presented problematic behaviors at mealtimes, with a predominance of food selectivity (57.8%), followed by changes in mealtime skills (34.4%), changes in masticatory motor skills (25.6%), oppositional eating behaviors (20.4%), and rigid eating behaviors (20.0%). Food selectivity was associated with excess body weight (PR: 1.94; 95% CI: 1.08–3.51) and absence of vegetable consumption (PR: 0.61; 95% CI: 0.46–0.81). Rigid eating behaviors was associated with low consumption of fiber (PR: 1.42; 95% CI: 1.15–1.75) and zinc (PR: 2.15; 95% CI: 1.33–3.45), and with excessive caloric (PR: 1.14; 95% CI: 1.02–1.29) and lower calcium intake (PR: 0.52; 95% CI: 0.29–0.91). Conclusion Selectivity and rigidity behaviors have different relationships with food consumption and are associated with a higher prevalence of inadequacies, which may lead to nutritional risks for children. Further studies may investigate the influence of problematic behaviors and excess body weight in ASD.